Application basis of combining antiangiogenic therapy with radiotherapy and immunotherapy in cancer treatment - Yuan, Meng; Zhai, Yirui; Hui, Zhouguang (Frontiers in Oncology, 2022)
How to further optimize the combination of radiotherapy and immunotherapy is among the current hot topics in cancer treatment. In addition to adopting the preferred dose-fractionation of radiotherapy or the regimen of immunotherapy, it is also very promising to add antiangiogenic therapy to this combination. We expound the application basis of cancer radiotherapy combined with antiangiogenic therapy and immunotherapy.